Hollow-Core Optical Fibre Technology: The Future Solution for Loss Reduction and High-Speed Data Transmission - Pradipto, Bimo; Rusdianti, Ishmah; Wijaya, Fairly; Oesman, Naufal; Sherila, Ayu (Indonesian Journal of Electrical Engineering and Electronics, 2025)
Hollow-core fibre (HCF) is the latest generation of optical fibre, featuring a hollow core structure that allows light to propagate through air or vacuum rather than through a glass core, as in conventional optical fibres. Utilising the principle of photonic bandgap or antiresonant guiding, HCF minimises attenuation and dispersion, making it ideal for high-speed, long-distance data transmission applications. This article discusses the physical and optical characteristics of HCF, advancements in fabrication processes, and its practical implementation in the field of optical communication. The study indicates that HCF has significant potential to replace conventional optical fibres in the future, particularly in backbone networks and latency-sensitive applications.